Minimal Algebras of Binary Operations of Rank 3 - Eremenko, Dmitry A. (Computer Tools in Education, 2020)
The problem of finding minimal algebras of binary operations of rank 3 is considered in this paper. Solving this problem is the first step for constructing a lattice of algebras of binary operations of rank 3. The construction of such a lattice is one of the problems of universal algebra, in particular, the theory of lattices. The article describes an algorithm for finding minimal algebras, which is based on the idempotency property of operations generating minimal algebras. This algorithm was implemented in Python. The results of the algorithm are presented in tabular form.
Keywords: operations; multioperations; lattice of algebras operations; minimal algebras of operations